PENGARUH STRATEGI GENIUS LEARNING DISERTAI METODE PENEMUAN TERBIMBING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP NEGERI 3 SUTERA TAHUN PELAJARAN 2013/2014 - Herayanti, Vitria; Rismen, Sefna; Cesaria, Anna (Pendidikan Matematika, 2014)
ABSTRACThe aim of the research was to study whether the understanding of mathematical concept of the students taught by using Genius Learning strategy with Guided Finding method was better than that of students taught by using conventional learning. This was an experimental research which used random toward the subject design. The population of the research was the students in class VIII of SMPN 3 Sutera registered in Academic Year 2013/2014. The data obtained was analyzed by using t-test on the significance level 0,05. Based on the result of data analysis, it was found that H0 was rejected signifying that the understanding of mathematical concept of the students taught by using Genius Learning strategy with Guided Finding method was better than that of students taught by using conventional learning in class VIII of SMPN 3 Sutera.